Synergy effects of highway investments on the Turkish economy: An application of an integrated transport network with a multiregional CGE model. (September 2020) - Piskin, Metin; Hewings, Geoffrey J.D.; Hannum, Christopher M.
Abstract: We develop a Multi-Regional Spatial Computable General Equilibrium (TurkSCGE) model for economic analysis of highway projects, estimating their impacts on regional welfare and economic outcomes in Turkey. The framework integrates a transport sub-model that estimates minimum distances with a multiregional Computable General Equilibrium model that estimates economic aggregates. TurkSCGE identifies eight sectors in each of 11 regions. Three experiments explore the impacts of decreases in transportation margins from 'distance shortening'. The three highway projects involved are estimated to yield a combined increase in GDP of 1.6%. However, the new highways in eastern Turkey, connecting eastern regions to each other and the west are shown to be best options for improving welfare in poorer regions. Highlights: Economic impact of transportation investment at the framework of multi regional computable general equilibrium modeling. Regional effects of public transportation investment. Transportation costs and regional economic growth. The impacts of transportation investments in Turkey. Spatial economic impacts of transportation infrastructure.